Efektivitas Siklus Penelitian Tindakan Kelas dalam Meningkatkan Pembelajaran: A Systematic Literature Review - NIA NADIFATUL ULA NIA; Azzarina Azka Humairoh Zarin; Arina Manasikana Arina; Itna Khusnatul Azizah Itna; Imron Fauzi Imron (Advances In Education Journal, 2026)
Classroom Action Research (CAR) is a reflective approach widely used to improve the quality of learning. Various studies have shown that the CAR cycle model, consisting of planning, action implementation, observation, and reflection, plays a crucial role in continuously improving learning practices. However, comprehensive studies synthesizing empirical evidence regarding the effectiveness of the CAR cycle model in improving learning quality are still limited. This study aims to analyze the effectiveness of the CAR cycle model in improving learning quality based on various previous research findings. This study used the Systematic Literature Review (SLR) method with reference to the PRISMA guidelines. Literature searches were conducted through the Scopus and Google Scholar databases with publications spanning 2015–2025. A total of 20 scientific articles that met the inclusion criteria were systematically analyzed to identify patterns of findings related to the implementation of the CAR cycle in learning. The results of the literature synthesis indicate that the CAR cycle model contributes significantly to improving learning quality, particularly in increasing student engagement, the effectiveness of learning strategies, and learning outcomes. The systematic integration of the planning, action implementation, observation, and reflection stages enables teachers to continuously improve learning based on empirical data. The contribution of this research lies in providing a comprehensive empirical synthesis regarding the effectiveness of the CAR cycle and providing a conceptual framework that can be a reference for teachers and researchers in implementing CAR as a strategy to improve the quality of learning.